For f(x) = 3x+1 and g(x) = x^2 – 6, find (f/g)(x)

Question

For f(x) = 3x+1 and g(x) = x^2 – 6, find (f/g)(x)

in progress 0
Anna 2 weeks 2021-11-10T04:31:06+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-10T04:33:03+00:00

    Answer:

    3x+\frac{1}{x^2}-6

    Step-by-step explanation:

    First establish that you need to find f(x) divided by g(x)

    Then substitute your two values into the equation above

    3x+1/x^{2}-6

    Then divide

    And you will get 3x+\frac{1}{x^2}-6

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )